Natureza e regime jurídicos da prescrição do art. 40, §4º, Lei 6.830/1980 - Kim, Hye Jin (2015)
This work aims to investigate the legal nature as well as the legal regime of intervening limitation provided by article 40, paragraph 4, Tax Execution Law, distinguishing it from the limitation of the article 174, National Internal Tax Code. Before studying limitation itself, we delimit the requirements, highlight the importance of language to understand and to create the reality, including the legal reality, harmonize several legal system studies, conceptualize rule of law and explain the correspondent classifications. We found that there is no general theory of limitation and this figure comes from a legal and positive concept, which means, it depends on a statutory provision to verify its nature. Given this conclusion, we separate the primary rule of limitation (substantive rule) from the secondary rule of limitation (procedure rule). We defend that article 40, paragraph 4, Tax Execution Law, is constitutional, extracting from it, choosing from the many interpretations possible, the one that is compatible with the Constitution. In this context, in order to differentiate these figures, we delimited the legal regime of the substantive rule of limitation, provided for article 174, National Internal Tax Code, with the tax constitutional principles, the requirement of declaratory statute to provide about it, as well as its application before, during and after the tax execution. We also outlined the legal regime of the procedure rule of limitation, provided for article 40, paragraph 4, Tax Execution Law, with the procedural constitutional principles and tax execution principles, the requirement of ordinary law, the adoption of the reception theory, the intertemporal issues, and the applicability of this provision by analogy to other situations